A micro-experimental insight into the mechanical behavior of sticky rice slurry-lime mortar subject to wetting-drying cycles - Yang, Rongwei; Li, Kefei; Wang, Linlin; Bornert, Michel; Zhang, Zhiling; Hu, Tao (Journal of materials science, 2016)
As an organic-inorganic composite material, sticky rice slurry-lime mortar (SLM) is being used more and more as a repair material in the preservation of cultural heritage. Taking advantage of environmental scanning electron microscopy and the digital-image correlation technique, the microdeformation and damage mechanisms of SLM subject to wetting/drying are investigated in this study. Three wetting-drying cycles between 20 and 98 % relative humidity (RH) are carried out with different hydric loading rates (i.e., 10 % RH/min, 40 % RH/min, instantaneous RH change). Micro-observation and full-field strain measurement are performed on a domain of size 400 × 345 μ m 2 . The results reveal that SLM subject to wetting-drying exhibits a heterogeneous strain field that correlates well with the heterogeneous microstructure of the SLM. In the first cycle, the global swelling strain is 0.25 % when RH increases from 20 to 98 %; when re-drying back to 20 % RH, we found an irreversible strain 0.04 %. The latter is demonstrated to arise from the propagation of pre-existing microcracks during the drying path. However, in the following two wetting-drying cycles, the microcracks become stable, and the irreversible strain changes slightly.